Optimizing the induction chemotherapy regimen for patients with locoregionally advanced nasopharyngeal Carcinoma: A big-data intelligence platform-based analysis. (April 2018) - Peng, Hao; Tang, Ling-Long; Chen, Bin-Bin; Chen, Lei; Li, Wen-Fei; Mao, Yan-Ping; Liu, Xu; Zhang, Yuan; Liu, Li-Zhi; Tian, Li; Guo, Ying; Sun, Ying; et al.
Abstract: Objectives: This study aimed at identifying the optimal induction chemotherapy regimen for patients with locoregionally advanced nasopharyngeal carcinoma (NPC) treated by intensity-modulated radiotherapy. Materials and methods: We identified eligible patients with newly-diagnosed stage III-IVA NPC (excluding T3N0) between September 2009 and May 2015. Survival outcomes and grade 3–4 toxicities were compared between different IC regimen groups. Results: In total, 3738 patients were eligible for this study, with 1572 (42.1%), 1085 (29.0%) and 1081 (28.9%) receiving TPF, PF and TP, respectively. In the whole population, multivariate analysis found that TPF seems to be better than PF and TP. Howerver, subgroup analysis revealed TPF and TP had same effectiveness in patients receiving a cumulative cisplatin dose (CCD) ≥ 200 mg/m 2 in concurrent chemotherapy, while TPF shows relatively better survival benefit in patients receiving CCD < 200 mg/m 2 . Grade 3–4 toxicities were similar between TPF and TP groups, but were relatively higher than that in PF group. Conclusions: Our study concluded that induction TP regimen may be enough for patients receiving a CCD ≥ 200 mg/m 2, while TPF may be superior to TP and PF for patients receiving a CCD < 200 mg/m 2, although grade 3–4 toxic events were more common but tolerable. Further studies are needed to validate our findings.